Fairness and persuasion: How stakeholder communication affects impartial decision making - Marco Kleine; Pascal Langenbach; Lilia Zhurakhovska (Max Planck Institute for Research on Collective Goods, 2014)
We study experimentally whether and to what extent impartial decision makers are influenced by stakeholders fairness opinions in an allocation decision. The setting allows for different focal fairness rules to be considered. We compare communication treatments, in which one of the stakeholders states his or her opinion prior to the allocation decision, to a baseline without communication opportunities. We find that stakeholders who state their opinion in the communication treatments are allocated significantly less money than their counterparts in the baseline. Asymmetric reactions to the statements appear to be the driving force behind this result: impartial decision makers deviate from their initial fairness judgment and follow stakeholders opinions only if the requests are moderate; they largely ignore high monetary claims. Our results contribute to understanding the underlying processes that may affect the decisions of judges, juries, arbitrators, referees, or other impartial decision makers in interaction with stakeholders.
Keywords: D63; D02; K40; C91; D03; 330; fairness; norms; communication; impartial decision maker; laboratory experiment; influence; persuasion